Transformation of Islamic Education: Implementation of Technological Innovation in Education Management - Fandir, A. (Jurnal Ilmiah Mandala Education (JIME), 2024)
This study reviews the context of Islamic education in the digital era with an emphasis on the role of Islamic philosophy and values in shaping educational paradigms. In this perspective, scientific studies illustrate the relationship between the principles of Islamic education and social and cultural values, as well as the urgency of the curriculum in the digital era. The analysis includes the concept of character education, family education based on the Koran. Apart from that, empowering human resources in managing Islamic education during the COVID-19 pandemic is a focus, with an emphasis on adaptation and resilience. The impact of globalization and technology on Islamic education, the integration of Al-Ghazali's concepts, and their role in shaping spiritual values and ethical awareness are also discussed. This synthesis of scientific work provides a comprehensive understanding of the challenges and opportunities in Islamic education in the digital era, providing valuable insights for educators, policy makers, and researchers. Finally, the study highlights the evolution of Islamic education, integrating values into modern practices, and illustrates the need for transformative approaches and technology integration in facing the modern educational context.